In Vivo Chemical Screen in Zebrafish Embryos Identifies Regulators of Hematopoiesis Using a Semiautomated Imaging Assay. (October 2016) - Arulmozhivarman, Guruchandar; Stöter, Martin; Bickle, Marc; Kräter, Martin; Wobus, Manja; Ehninger, Gerhard; Stölzel, Friedrich; Brand, Michael; Bornhäuser, Martin; Shayegi, Nona
Hematopoietic stem and progenitor cells (HSPCs) generate all cell types of the blood and are crucial for homeostasis of all blood lineages in vertebrates. Hematopoietic stem cell transplantation (HSCT) is a rapidly evolving technique that offers potential cure for hematologic cancers, such as leukemia or lymphoma. HSCT may be autologous or allogenic. Successful HSCT depends critically on the abundance of engraftment-competent HSPCs, which are currently difficult to obtain in large numbers. Therefore, finding compounds that enhance either the number or the activity of HSPCs could improve prognosis for patients undergoing HSCT and is of great clinical interest. We developed a semiautomated screening method for whole zebrafish larvae using conventional liquid handling equipment and confocal microscopy. Applying this pipeline, we screened 550 compounds in triplicate for proliferation of HSPCs in vivo and identified several modulators of hematopoietic stem cell activity. One identified hit was valproic acid (VPA), which was further validated as a compound that expands and maintains the population of HSPCs isolated from human peripheral blood ex vivo. In summary, our in vivo zebrafish imaging screen identified several potential drug candidates with clinical relevance and could easily be further expanded to screen more compounds.